2023
DOI: 10.21203/rs.3.rs-3423408/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Outbreak of malaria in southern Iran: How could manage this disease?

Mohammad khammarnia,
Mostafa Peyvand,
Esagh Barfar
et al.

Abstract: Background Iran is considered one of the countries with high rates of malaria, particularly in its southern and southeastern regions. In 2009, Iran initiated a program aimed at eliminating malaria by 2025. Proper management of the disease requires a complete knowledge of the disease. The objective of this study was to examine the malaria situation in southern Iran from 2016 to 2023. Method A cross-sectional study was carried out in Sistan-Baluchistan province as the second largest province of Iran in 2023. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Studies indicated that MEs are rarely reported [1]. Indeed MEs are a significant threat to patients' safety and a significant challenge that healthcare providers face worldwide [2]. Numerous individuals are victims of MEs in all countries [3].…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicated that MEs are rarely reported [1]. Indeed MEs are a significant threat to patients' safety and a significant challenge that healthcare providers face worldwide [2]. Numerous individuals are victims of MEs in all countries [3].…”
Section: Introductionmentioning
confidence: 99%